ARTIFICIAL INTELLIGENCE IN SMARTWATCHES : HOW PRODUCT AND SERVICE QUALITY SHAPE USER SATISFACTION THROUGH AI TRUST - Siahaya, Janice Carysa; Agape, Nicholas (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
Artificial intelligence (AI) has revolutionized various industries, including wearable technology. Garmin has integrated AI into its smartwatch products, enhancing user interactions and service quality. This study aims to analyze the impact of product quality, AI-enabled service quality, perceived convenience, and perceived ease of use on user satisfaction, with AI user experience and AI trust as mediating variables among Garmin smartwatch users in Surabaya. A quantitative approach was employed using an explanatory research design. Data were collected through an online survey of 144 Garmin smartwatch users in Surabaya, selected via snowball sampling. The data were analyzed using SPSS version 22.0. Respondents consisted of men and women aged 18–60 who had used a Garmin smartwatch regularly for at least three months. The findings indicate that Product Quality, AI Enabled Service Quality, Perceived Ease of Use significantly influence AI trust and AI trust has a significant impact on user satisfaction. However Perceived Convenience do not significantly affect AI Trust. These findings provide valuable insights for the development of AI-driven wearable technology and its impact on AI trust.